(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe clinical and paraclinical characteristics and outcomes of managing pregnant women with placenta previa at A Thai Nguyen Hospital. Methods: A cross-sectional descriptive study of 84 pregnant women with placenta previa based on clinical and ultrasound findings, with a gestational age of 28 weeks or more, conducted from 01 June 2022 to 31 May 2025 at A Thai Nguyen Hospital. Results: Placenta previa is most common in pregnant women aged 25–34 years old, accounting for 56.0%, 72.6% were multigravida, 64.3% were previous cesarean. Clinical features included vaginal bleeding in 59.5% of all cases, 47.6% had complete placenta previa. The cesarean delivery rate was 95.2%. X-stitch sutures at the placental attachment site, accounting for 58.8%. The mean gestational age at delivery was 37.2 ± 1.9 weeks. Conclusion: Vaginal bleeding is a common symptom of placenta previa. The rate of successful hemostasis in the study was high (95.0%).